Increased circulating cytokines in patients with myocarditis and cardiomyopathy. Issue 6 (December 1994) - Matsumori, A; Yamada, T; Suzuki, H; Matoba, Y; Sasayama, S
Abstract : OBJECTIVES--To elucidate the potential role of cytokines in the pathogenesis of cardiomyopathy and myocarditis. BACKGROUND--Experimental studies show that certain cytokines depress myocardial contractility and that tumour necrosis factor-alpha plays an important part in the pathogenesis of myocardial injury in animal models of viral and autoimmune myocarditis. METHODS--Plasma interleukin 1-alpha, interleukin 1-beta, interleukin-2, interleukin-6, tumour necrosis factor-alpha, tumour necrosis factor-beta, granulocyte-macrophage colony stimulating factor, granulocyte colony stimulating factor, macrophage colony stimulating factor, interferon-alpha and interferon-gamma were measured in 13 patients with acute myocarditis, 23 patients with dilated cardiomyopathy, 51 patients with hypertrophic cardiomyopathy, nine patients with acute myocardial infarction, 18 patients with angina pectoris, 12 patients with essential hypertension and 17 healthy controls. RESULTS--Increased concentrations of cytokines were not detected in the controls. In patients with acute myocarditis, interleukin 1-alpha was detected in 23% (mean (SD) 25 (11) pg/ml), tumour necrosis factor-alpha in 46% (61 (31) pg/ml), and macrophage colony stimulating factor was 2.5 (1.8) ng/ml (normal 1.9 (0.4)). In patients with dilated cardiomyopathy, tumour necrosis factor-alpha was detected in 35% (402 (555) pg/ml). In patients with hypertrophic cardiomyopathy, interleukin-2 was detectable in 14% (2318 (4738) pg/ml) and tumour necrosis factor-alpha ws detected in 20% (992 (1517) pg/ml). The concentration of macrophage colony stimulating factor was raised in patients with acute myocardial infarction. Granulocyte colony stimulating factor was often increased in myocarditis, cardiomyopathies, acute myocardial infarction, and angina pectoris--suggesting activation of macrophages and/or endothelial cells--but this increase was not specific to these diseases. Increased concentrations of cytokines were not found in patients with essential hypertension. CONCLUSION--These results suggest that cytokines may play a part in the pathogenesis of myocardial injury in myocarditis and cardiomyopathies and that further studies to explore the potential pathogenetic role of cytokines in myocardial diseases may be warranted.